Estetica forense, investigativa, politica: la costruzione di un nuovo senso comune (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Two books by Eyal Weizman — written together one with Thomas Keenan and the other with Matthew Fuller – make it possible to take a retrospective look at what was initially presented as ‘forensic aesthetics’ and has now been brought back to the proceedings of an ‘investigative aesthetics’. Considered as a whole, forensic and investigative aesthetics is one of the most interesting perspectives opened up in the field of aesthetics in this early part of the 21st century. It is a synthesis that brings together a series of disparate demands that have emerged on the social, political and philosophical levels with the thought of difference and with the questioning of the centrality of Western culture, sometimes confronted with its claims to colonial domination, sometimes dragged into contradictions that verge on caricature. The challenge of forensic, investigative aesthetics consists in rediscovering precisely at the aesthetic level the opportunities for a common feeling (“aesthetic commons”) in order to create a shared space beyond the classic distinction between the private and public spheres. Investigative and forensic aesthetichs focuses on the constitution of material culture, in particular on the production of images and their processual, constructive nature. Therefore, a critical approach becomes also a political proposition relying on the legibility of creative processes and offering to multiple communities formed on a case-by-case basis not the already constituted truth of a final evidence, an image for example, but precisely the formation process of a common sense. The undertaking is ambitious. Reconstructing some of its steps can be useful to determine its aspirations and better understand its theoretical path.